TOURISM GOVERNANCE CRISIS (A Study on the Kampung Ketupat Tourism Destination, 2024) - Hamidah, Siti; Wardiyanto, Bintoro; Nugroho, Kris; Kristanto, Budi (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
gb777